Pengaruh Harga dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Logam Mulia di PT. Antam Tbk UBPP Logam Mulia - Aulia Nur Syahrani; Elmira Siska (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
In a global economic situation full of uncertainty, gold is one of the most popular investment instruments because it is considered stable and has a high intrinsic value. PT Antam Tbk UBPP Precious Metals is one of the precious metal providers trusted by the public. However, purchasing decisions are not only influenced by product quality, but also by price and customer trust factors. This study aims to determine the effect of price and customer trust on purchasing decisions for precious metals at PT Antam Tbk UBPP Precious Metals. This study uses quantitative statistical methods with data collection techniques through questionnaires to 110 respondents selected using purposive sampling techniques, namely respondents who have purchased gold at PT Antam Tbk directly or online. Data analysis was carried out by validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis testing and coefficient of determination test using SPSS version 25. This research was conducted from April-June 2025. The results showed that the price partially had a positive and significant effect on purchasing decisions (3,728>1,982). customer trust also partially had a positive and significant effect on purchasing decisions (6,591>1,982) and price and customer trust simultaneously had a positive and significant effect on the decision to purchase precious metals at PT Antam Tbk UBPP Precious Metals (69,693>3,08).